The response of pigs to diets containing varying levels of cocoa placenta meal (CPM) supplemented with an exogenous enzyme complex - John Dafaar Damsere; Michael Boateng (African Journal of Pig Farming, 2022)
A nineteen-week experiment was conducted to establish the effects of an enzyme supplementation on growth performance, economics of production, carcass components and blood profile of pigs fed diets containing different levels of cocoa placenta meal (CPM). Twenty-five Large White grower pigs with mean initial live weight of 15.4 kg were randomly allocated to five treatments: T1 (0% CPM), T2 (5% CPM), T3 (10% CPM), T4 (15% CPM) and T5 (20% CPM) in a randomized complete block design (RCBD). Diet T1 had no enzyme but diets T2, T3, T4 and T5 contained 35 g enzyme per 100 kg feed. Each treatment had five pigs and each pig served as a replicate. Feed and water were provided ad-libitum. Pigs were slaughtered upon the attainment of a live weight of 70 ± 2.5 kg for carcass studies. Blood samples were collected during slaughtering. Feed cost (€ per kg) was inversely proportional to the inclusion level of the CPM + enzyme. Pigs on the T1 and T2 diets utilized their feed more efficiently (p < 0.05) than those on the T3, T4 and T5. However, no differences (p > 0.05) were observed in the variations of the feed cost per kg gain values recorded. The CPM + enzyme inclusion resulted in decreased values (p < 0.05) for backfat thickness. There were no dietary (p ˃ 0.05) effects on the blood profile. Dietary inclusion levels up to 20% CPM + enzyme can be fed to growing-finishing pigs without any detrimental effects on most of the growth performance and carcass criteria.